REALISASI CORPORATE SOCIAL RESPONSIBILITY DALAM PERSPEKTIF HUKUM LINGKUNGAN - Adristy, Dinda Bethari; Rr. Ani Wijayati; Paltiada Saragi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
In general, Corporate Social Responsibility is only held out by companies that work in the field of natural resources and tends to be mandatory. However, there is no regulation related to CV in the Limited Liability Law, considering that CV is a part of non-legal entity. Based on the description above, the lies behind applying corporate social responsibility towards CV XXX XXXXX XXXXX in the perspective of Environmental Law and how the judges of the Lubuk Sikaping District Court considered their judgments through the case Number XX/Pdt.G/XXXX/PN XXX. The research method used a normative juridical research, which is research that uses a method of examining library materials or library sources in the form of written legal norms and applicable positive law. The analysis was based on the statue approach used to discover the entire legal regulation on environmental pollution in particular in Indonesia. Thereafter, the author used the concept approach and the case approach. The results of the study indicate that non-legal entities such as CV, are recommended to implement the Corporate Social Responsibility programs since the CV own a business in the field of natural resources and should be issued several significant documents, such as AMDAL, UKL-UPL, and SPPL, right before applying for the Mining Business Permit (IUP) to the Minister of Energy and Mineral Resources, the Governor, or the Regent/Mayor where the mining area is located based on the application they submitted, in addition to minimizing unwanted events related to the environment around the mining area.